Cognitive behavioural therapy for depression: systematic review of imaging studies. Issue 2 (30th June 2015) - Franklin, George; Carson, Alan J; Welch, Killian A.
Abstract : Objective: Although cognitive behavioural therapy (CBT) has been shown to be an effective treatment for depression, the biological mechanisms underpinning it are less clear. This review examines if it is associated with changes identifiable with current brain imaging technologies. Methods: To better understand the mechanisms by which CBT exerts its effects, we undertook a systematic review of studies examining brain imaging changes associated with CBT treatment of depression. Results: Ten studies were identified, five applying functional magnetic resonance imaging, three positron emission tomography, one single photon emission computer tomography, and one magnetic resonance spectroscopy. No studies used structural MRI. Eight studies included a comparator group; in only one of these studies was there randomised allocation to another treatment. CBT-associated changes were most commonly observed in the anterior cingulate cortex (ACC), posterior cingulate, ventromedial prefrontal cortex/orbitofrontal cortex (VMPFC/OFC) and amygdala/hippocampus. Discussion: The evidence, such as it is, suggests resting state activity in the dorsal ACC is decreased by CBT. It has previously been suggested that treatment with CBT may result in increased efficiency of a putative 'dorsal cognitive circuit', important in cognitive control and effortful regulation of emotion. It is speculated this results in an increased capacity for 'top-down' emotion regulation, which is employed when skills taught in CBT are engaged. Though changes in activity of the dorsal ACC could be seen as in-keeping with this model, the data are currently insufficient to make definitive statements about how CBT exerts its effects. Data do support the contention that CBT is associated with biological brain changes detectable with current imaging technologies.